Characterisation of Microstructure of We43 Magnesium Matrix Composites Reinforced with Carbon Fibres - Gryc A.; Rzychoń T. (Archives of Metallurgy and Materials, 2016)
In the paper the microstructures of WE43 matrix composites reinforced with carbon fibres have been characterised. The influence of reinforcement type and T6 heat treatment (a solution treatment at 525°C for 8 h, a hot water quench and a subsequent ageing treatment at 250°C for 16 h) on microstructure have been evaluated. The light microscope and scanning electron microscope investigations have been carried out. No significant differences in samples reinforced with non-coated textiles have been reported. The substantial changes in sample reinforced with nickel-coated textile have been observed. The segregation of alloying elements to the matrix-reinforcement layer has been identified. The T6 heat treatment caused the appearance of disperse precipitates of β phase, but the process cannot be considered as satisfactory (irregular distribution, low volume fraction, relatively large size).